Bioactivity of Mikania micrantha extract in controlling Erwinia chrysanthemi: a natural antibacterial approach (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Crop losses caused by soft rot disease induced by Erwinia chrysanthemi pose a persistent threat to global agricultural productivity. Excessive use of synthetic chemical pesticides to control such bacterial diseases has raised serious environmental and health concerns due to their residual toxicity and ecological impact. As an alternative, plant-derived biopesticides have gained attention for their biodegradability, safety, and sustainability. This study aimed to evaluate the antibacterial activity of Mikania micrantha Kunth (sembung rambat) leaf extract against E. chrysanthemi and to determine the most effective concentration for bacterial inhibition. The antibacterial assay was performed using the Kirby–Bauer disc diffusion method with five treatments and four replications: three concentrations of M. micrantha leaf extract (25%, 50%, and 80%), a positive control (1% chloramphenicol), and a negative control (sterile distilled water). Data were analyzed using analysis of variance (ANOVA) and Duncan’s Multiple Range Test (DMRT) at a 95% confidence level.The results showed that M. micrantha extract exhibited moderate antibacterial activity, producing inhibition zones of 7.51 mm, 8.02 mm, and 8.40 mm for 25%, 50%, and 80% concentrations, respectively. Although inhibition increased with concentration, the differences among extract treatments were not statistically significant (p > 0.05). The positive control exhibited a much larger inhibition zone (30.95 mm), while the negative control showed none.These findings indicate that M. micrantha leaf extract possesses moderate antibacterial potential against E. chrysanthemi and may serve as a promising plant-based biocontrol agent for sustainable disease management.
Keywords: Erwinia chrysantemi; Mikania micrantha; pesticide; soft rot disease